Question
Asked Sep 29, 2019
7 views
Let f(x)= -5x-1 and g(x)- x2- 5.
Find (f o g)-5).
Then (fo g)(-5) = | |. (Simplify your answer.)
help_outline

Image Transcriptionclose

Let f(x)= -5x-1 and g(x)- x2- 5. Find (f o g)-5). Then (fo g)(-5) = | |. (Simplify your answer.)

fullscreen
check_circle

Expert Answer

Step 1

Given,

...
help_outline

Image Transcriptionclose

f(x)5x 1 and g(x) = x2 - 5 Now, fog(x) f(g(x)) - f(x2 - 5) =-5(x2 5) 1 — -5х2 + 25 ——1 = -5x2 + 24 fog(-5) = -5(-5)2 24 = -125 24 =-101

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Algebra